Analysis of Generation Z's Understanding of the Lolik Lalen Fedak Fena symbol Against the Development of Education in Namrole District, South Buru Regency - Naldo Seleky; Lisye Salamor; Jumiati Tuharea (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is a qualitative descriptive study that aims to determine the meaning of the cultural symbol lolik lalen fedak fena for generation Z, to determine generation Z's understanding of the lolik lalen fedak fena symbol and to determine the relationship between the lolik lalen fedak fena symbol and the development of education in Namrole District, South Buru Regency . This research was conducted in Namrole District. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved. Data collection techniques used are observation, interviews and documentation. The results of this interview can show that the lolik lalen fedak fena symbol which is a unifying symbol for the people of Namrole District has a very important meaning and significance for the life of the people of Namrole District. Where the meaning of this symbol is to unite the heart to build the country. The implied meaning behind this symbol is to remain united in heart, hand in hand, in building the country regardless of race, ethnicity, religion and culture. This symbol is a unifying principle for the people of Namrole, just as Pancasila is the way of life for the Indonesian people, the people of Namrole District, whose culture is still so strong that it makes Namrole District an area that adheres to culture and continues to maintain and preserve what has become the pride of the community as a community. rich in culture. A culture that both want to build without having to look at each other's backgrounds or differences. This symbol is present in the midst of existing diversity or diversity as a unifying symbol. Because the people of Namrole have the belief that without unity there will be no progress.